2008
DOI: 10.1523/jneurosci.5671-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Robos and Slits Control the Pathfinding and Targeting of Mouse Olfactory Sensory Axons

Abstract: Odorants are detected by olfactory receptor neurons (ORNs) located in the olfactory epithelium. In mice, ORNs expressing the same odorant receptor (OR) project to a single glomerulus out of 1800 in the olfactory bulb (OB). It has been proposed that OR-derived cAMP signals guide ORN axons to their glomeruli rather than OR themselves. Recently, it has also been shown that the axon guidance molecule Slit1 and its receptor Robo2 control the dorsoventral segregation of ORN axons as they are projecting to the OB. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 34 publications
6
75
0
Order By: Relevance
“…S1A,B). Consistent with previous reports (Nguyen-Ba-Charvet et al, 2008), immunostaining in E16 brain sections from mice showed that Slit-2 was highly expressed in apical cells of the OE (Fig. 1D).…”
Section: Robo1 Is Expressed In Oecs Both In Vitro and In Vivosupporting
confidence: 92%
See 2 more Smart Citations
“…S1A,B). Consistent with previous reports (Nguyen-Ba-Charvet et al, 2008), immunostaining in E16 brain sections from mice showed that Slit-2 was highly expressed in apical cells of the OE (Fig. 1D).…”
Section: Robo1 Is Expressed In Oecs Both In Vitro and In Vivosupporting
confidence: 92%
“…Recent studies have shown that glial cell migration can also be directed by some axon guidance molecules (Tsai and Miller, 2002). Because OECs share a common origin (olfactory placode) with olfactory sensory neurons and migrate out from the OE to the OB together with olfactory sensory axons during the same developing period (Valverde et al, 1992), it is likely that guidance cues for olfactory sensory axons, like Slit (Cho et al, 2007;Nguyen-Ba-Charvet et al, 2008), might also guide the migration and distribution of OECs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In robo2 mutant zebrafish, glomerular spatial arrangements in the main olfactory system are also impaired (Miyasaka et al, 2005). The mistargeting of OSN axons is even more obvious in Robo1/Robo2 and Slit1/Slit2 double-null mice, in which OSNs that express the same odorant receptors project on to multiple glomeruli (Nguyen-Ba-Charvet et al, 2008) (Fig. 3C).…”
Section: Reviewmentioning
confidence: 97%
“…1B). Mice deficient for Robo-2 have defective axonal projections along the D-V axis (Cho et al 2007;Nguyen-Ba-Charvet et al 2008).…”
Section: Mechanisms Of Olfactory Map Formation In Mammals Topographicmentioning
confidence: 99%